2019
DOI: 10.1021/jacs.9b01589
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Reaction Mechanisms of SiO Anodes for Li-Ion Batteries by Combining in Situ 7Li and ex Situ 7Li/29Si Solid-State NMR Spectroscopy

Abstract: Silicon monoxide is a promising alternative anode material due to its much higher capacity than graphite, and improved cyclability over other Si anodes. An in-depth analysis of the lithium silicide (Li x Si) phases that form during lithiation/delithiation of SiO is presented here and the results are compared with pure-Si anodes. A series of anode materials is first prepared by heating amorphous silicon monoxide (a-SiO) at different temperatures, X-ray diffraction and 29 Si NMR analysis revealing that they comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 54 publications
(222 reference statements)
7
118
0
1
Order By: Relevance
“…[8][9][10] One of these methods, in situ or operando SSNMR of Li and Na nuclei, is also suitable for characterizing the negative electrode in LIBs and NIBs 11,12 as Li/Na NMR can be used to observe the entire Li or Na nuclei in samples containing nuclei stored in the inner structure of materials, which are not easily observed directly by SEM or X-ray analyses. For the negative electrode materials of LIBs and NIBs, the behaviour of Li [13][14][15][16][17][18][19][20] and Na 21 in carbon electrodes and metal electrodes [22][23][24][25][26][27][28] have been observed using in situ or operando NMR. Very recently, in situ magic angle spinning (MAS) NMR was also realized.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…[8][9][10] One of these methods, in situ or operando SSNMR of Li and Na nuclei, is also suitable for characterizing the negative electrode in LIBs and NIBs 11,12 as Li/Na NMR can be used to observe the entire Li or Na nuclei in samples containing nuclei stored in the inner structure of materials, which are not easily observed directly by SEM or X-ray analyses. For the negative electrode materials of LIBs and NIBs, the behaviour of Li [13][14][15][16][17][18][19][20] and Na 21 in carbon electrodes and metal electrodes [22][23][24][25][26][27][28] have been observed using in situ or operando NMR. Very recently, in situ magic angle spinning (MAS) NMR was also realized.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…An 'obvious' win involves replacing graphite with either silicon or silicon oxide, due to their fivefold-tenfold higher energy densities. However, this is not straightforward: SiO x causes considerable first cycle irreversibly capacity loss associated with the formation of inorganics such as Li 2 O and Li 4 SiO 4 7 . A stable SEI Methods for mitigating degradation Heat treatments of surface-coated materials can be used to prepare surface-doped materials with improved chemical stability and that inhibit the growth of surface rocksalt layers.…”
Section: Optimisation Of Current Commercial and Related Chemistriesmentioning
confidence: 99%
“…Due to the highest volume energy density and the outstanding cycling performance, LiCoO 2 (LCO) materials have dominated the field of consumer electronics markets for more than 30 years. The local environment changes of lithium and cobalt atoms in LCO electrode have been investigated by 6/7 Li and 59 Co MAS NMR. [37] 7 Li NMR signal exists at 0 ppm for the pristine LCO material because of the diamagnetic environment of Li + .…”
Section: Lithium Cobalt Oxidementioning
confidence: 99%
“…[37c] There are few studies about the influence of aliovalent doping on the local environment in the process of (de) lithiation for LCO. More recently, Wan et al have systematically studied the structure evolution of the Al doping and Al/La co-doping LCO electrodes through 6 Li/ 59 Co MAS NMR, in situ XRD and XPS measurements. [38] Their 7 Li NMR results showed that undoped LCO only has one narrow single phase at positive shift during charge process while Al-LCO and Al/La-LCO displays a distinctly asymmetrical peak, indicating that Al/La co-doping would induce more local structural phase and more continuous phase evolution than single Al doping LCO sample, and much more than the undoped LCO sample during cycling, which postpones the appearance of H1-3 phase and alleviates the volume change at high-voltage above 4.2 V.…”
Section: Lithium Cobalt Oxidementioning
confidence: 99%